2022
DOI: 10.1097/fch.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Social Determinants of Health and Adolescent Contraceptive Use

Abstract: This research assessed social determinants of contraceptive use among a nationally representative sample of adolescents. This study analyzed nationally representative, publicly available data from the 2013-2015 National Survey of Family Growth (NSFG). The sample consisted of sexually active males and females between the ages of 15 and 19 (n = 775). Independent variables were social determinant questions asked on the NSFG, selected based on the Healthy People Social Determinants of Health Framework. We tested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In keeping with prior research, 5,14,24 the current study found that having a usual source of care increased contraceptive options. Unlike a prior national study, 5 we did not find having usual care to predict the use of any contraception.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In keeping with prior research, 5,14,24 the current study found that having a usual source of care increased contraceptive options. Unlike a prior national study, 5 we did not find having usual care to predict the use of any contraception.…”
Section: Discussionsupporting
confidence: 84%
“…Neither EDs nor urgent care clinics focus on reproductive health or connect patients with individual providers over time 7–10 . However, we believe that the limited number of contraceptive differences we found across sources of usual care, and scarce prior evidence of such differences, 5,14,24 in the context of increasing numbers of people without a usual source of primary care, imply re-examining how emergent as well as primary care settings can improve contraceptive access.…”
Section: Discussionmentioning
confidence: 80%
“…The data on teen sexual activity, contraceptive use, and childbearing presented in this report are shown with respect to several key demographic characteristics of the respondent. Three measures of teenagers' families of origin are included because they have well-documented associations with sexual activity and the use of contraception among teenagers, partly through their strong correlation with family socioeconomic status: mother's educational attainment, the age when the mother had her first child, and parental living arrangements (that is, parental presence or absence in the teenager's household) (22)(23)(24).…”
Section: Measures Of Demographic Characteristics and Parental Backgroundmentioning
confidence: 99%
“…In addition, concern remains high over the incidence of HIV and other sexually transmitted infections (STIs) among young people. Sexually active adolescents and young adults (ages [15][16][17][18][19][20][21][22][23][24] are at higher risk of acquiring STIs than adults for reasons that include behavior, physiology, and factors related to healthcare access and services (9). Prevalence estimates suggest that one in four sexually active adolescent females has an STI, such as chlamydia or human papillomavirus (9).…”
Section: Introductionmentioning
confidence: 99%